Reforming Energy Policy in India : Assessing the Options - Parry, Ian (IMF Working Papers; Working Paper ;, 2017)
Spreadsheet models are used to assess the environmental, fiscal, economic, and incidence effects of a wide range of options for reducing fossil fuel use in India. Among the most effective options is ramping up the existing coal tax. Annually increasing the tax by INR 150 (USD 2.25) per ton of coal from 2017 to 2030 avoids over 270,000 air pollution deaths, raises revenue of 1 percent of GDP in 2030, reduces CO2 emissions 12 percent, and generates net economic benefits of approximately 1 percent of GDP. The policy is mildly progressive and (at least initially) imposes a relatively modest cost burden on industries.